Long-lasting beneficial effects of central serotonin receptor 7 stimulation in female mice modeling Rett syndrome - De Filippis, Bianca; Chiodi, Valentina; Adriani, Walter; Lacivita, Enza; Mallozzi, Cinzia; Leopoldo, Marcello; Domenici, Maria Rosaria; Fuso, Andrea; Laviola, Giovanni (Frontiers in Behavioral Neuroscience, 2015)
Rett syndrome (RTT) is a rare neurodevelopmental disorder, characterized by severe behavioral and physiological symptoms. Mutations in the methyl CpG binding protein 2 gene (MECP2) cause more than 95% of classic cases, and currently there is no cure for this devastating disorder. Recently we have demonstrated that specific behavioral and brain molecular alterations can be rescued in MeCP2-308 male mice, a RTT mouse model, by pharmacological stimulation of the brain serotonin receptor 7 (5-HT7R). This member of the serotonin receptor family – crucially involved in the regulation of brain structural plasticity and cognitive processes – can be stimulated by systemic repeated treatment with LP-211, a brain-penetrant selective 5-HT7R agonist. The present study extends previous findings by demonstrating that the LP-211 treatment (0.25 mg/kg, once per day for 7 days) rescues RTT-related phenotypic alterations, motor coordination (Dowel test), spatial reference memory (Barnes maze test) and synaptic plasticity (hippocampal long-term-potentiation) in MeCP2-308 heterozygous female mice, the genetic and hormonal milieu that resembles that of RTT patients. LP-211 also restores the activation of the ribosomal protein S6, the downstream target of mTOR and S6 kinase, in the hippocampus of RTT female mice. Notably, the beneficial effects on neurobehavioral and molecular parameters of a seven-day long treatment with LP-211 were evident up to two months after the last injection, thus suggesting long-lasting effects on RTT-related impairments. Taken together with our previous study, these results provide compelling preclinical evidence of the potential therapeutic value for RTT of a pharmacological approach targeting the brain 5-HT7R.